Crystal engineering of three-dimensional frameworks of cobalt(II) and copper(II) coordination polymers constructing from azopyridine and phenylenediacetic acid ligands - Ha, Jintae; Boonmak, Jaursup; Youngme, Sujittra (KKU Science Journal, 2017)
The cobalt(II) and copper(II) coordination polymers constructed fromazopyridine and phenylenediacetic acid as ligands, [Co2(ppda)2(azp)2]n (1), and [Cu(ppda)(azp)]n (2) when azp=4,4’-azobis(pyridine),ppda=1,4-phenylenediacetate,are successfully synthesized and characterized by CHN analysis, IR, PXRD, TGA and single crystal X-ray diffraction. Compound 1 exhibits a 3D framework with dinuclear [Co2(COO)2] secondary building unitswhile 2 is a 2-fold interpenetrated 3D coordination polymer with paddle-wheel dinuclear [Cu2(COO)4] secondary building units, both are different in structural architecture.